THE EFFECT OF PARTICIPATION IN JKN ON UNMET NEEDS FOR HEALTHCARE SERVICES - Farikh Alfa Firori; I Dewa Gede Karma Wisana (Universitas Airlangga, 2023)
Background: The National Health Insurance or Jaminan Kesehatan Nasional (JKN) program is one of the steps taken by the Indonesian government in developing Universal Health Coverage (UHC). However, increased participation in the National Health Insurance is not followed by an increase in met needs for healthcare services. Aims: This study aimed to examine the effect of participation in the National Health Insurance on unmet needs for healthcare services in poor and non-poor population groups. Methods: This study used data from the 2018 National Socio-Economic Survey/ Survei Sosial Ekonomi Nasional (SUSENAS) and Village Potential Survey/ Survei Potensi Desa (PODES). Data were processed using binary logistic model analysis to identify the effect of participation in the National Health Insurance on the unmet needs for healthcare services. Results: Participation in the National Health Insurance, including beneficiary program for poor groups could reduce the risks of unmet needs for healthcare services by 7.7%, while non-beneficiary program could reduce the risks of unmet needs for health services for non-poor groups by 10.4%. Conclusion: Both beneficiaries and non-beneficiaries affect the unmet needs for health services for both poor and non-poor groups. However, the non-beneficiary program is more elastic than beneficiary program to fulfill needs for both sample groups. Keywords: Healthcare services, national health insurance, logit, unmet need